2022
DOI: 10.3389/fpsyg.2022.877072
|View full text |Cite
|
Sign up to set email alerts
|

Social Integration in Higher Education and Development of Intrinsic Motivation: A Latent Transition Analysis

Abstract: This study, based on the self-determination theory, investigates the link between university students' social peer and teacher integration and intrinsic motivation development. Both integration contexts are expected to contribute to the student's development, either additive or compensatory. The analyses rely on a nationally representative sample of 7,619 German university students (NEPS data set) and cover the time between the 3rd and 5th semesters in a longitudinal design. Person-centered analytical tools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Our results also suggested that students’ perceived integration into their college environment socially and academically differ across their motivation profiles after controlling for their demographic and pre-college academic characteristics. This finding is consistent with previous studies that motivation is positively associated with academic and social integration (Reindl et al, 2022). Our study expands the existing literature by applying a person-centered approach to capture a more comprehensive picture of motivation profiles for individuals.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results also suggested that students’ perceived integration into their college environment socially and academically differ across their motivation profiles after controlling for their demographic and pre-college academic characteristics. This finding is consistent with previous studies that motivation is positively associated with academic and social integration (Reindl et al, 2022). Our study expands the existing literature by applying a person-centered approach to capture a more comprehensive picture of motivation profiles for individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Próspero and Vohra-Gupta (2007) reported that dimensions of motivation (i.e., intrinsic, extrinsic, and amotivation) and integration (i.e., academic and social) significantly contributed to academic achievement for FGCS. Reindl et al (2022) come the closest in their examination of motivational trajectories and integration profiles using person-centered analytic tools, but FGCS were not targeted in their study. In this current study, we focus on identifying FGCS' academic motivation profiles through a person-centered approach and exploring the association between participants' college integration, commitment, and persistence intentions across different motivation profiles.…”
Section: Fgcs Academic Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings show that education is a major instrument for the transmission of cultural values, norms (Nakata & Takezawa, 2023;Pedroso et al, 2023), knowledge and essential skills (Cheng, 2021). At the same time, education facilitates social integration and contributes to socialization (Reindl et al, 2022), and fosters a sense of national identity among country's citizens (Hsieh, 2020;Matafora et al, 2021). Education also increases social order, reinforces established system of rules, and promotes the building of law-based society (Dong & Zeb, 2022;Vodolaskova, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%